Effect of Carrier Frequency in Grid Inter Connected Wind System With SSFC Controller - Samanthaka Mani Kuchibhatla; D Padmavathi; R Srinivasa Rao (Institute of Advanced Engineering and Science, 2018)
In this paper a grid interconnected system with wind energy source linked with a FACTs based SSFC device ( Static switched filter compensator ) at load for enhancing power quality is considered .Analysis is done for the proposed system by varying Carrier frequency over a wide range and observed system performance at all 3 busses wise Grid bus, Generator Bus and Load Bus. Two regulators are used to organize the FACTS SSFC-device, these are based on a tri-loop dynamic error obsessed inter-coupled input to VSC controller. Investigation is made in MATLAB/SIMULINK Environment for the proposed system ,it is observed that system performance in terms of percentage Total harmonic Distortion is satisfactory along with the Enhanced Power Quality.